2022
DOI: 10.1088/1742-6596/2411/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Ex-situ doping of ZnO structures as potential random lasers

Abstract: Zinc oxide (ZnO) nanorods were formed on a glass substrate using chemical bath deposition (CBD) method for three hours at 96 °C. Doping of aluminum (Al) was realised by dipping into aluminum nitrate solution. XRD spectra shows reduced (002) peak related to the crystallinity of the synthesized ZnO with increasing doping concentrations. Doping with 35 mM exhibited highest Al concentration of 11.78 %. An apparent shift in bandgap energy with increasing doping concentration provides further evidence of doping occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…On behalf of its merits arising from the randomness, a random laser intrinsically has difficulties in controlling its lasing characteristics such as frequency mode, emission intensity, and spatial radiation pattern. Some approaches for passive control of random lasing characteristics, i.e., the modification of scattering properties by designing an adequate random structure, have been reported: For example, Fujiwara et al demonstrated that introducing a defect point of a polystyrene sphere into homogeneous random media consisting of spherical nanoparticles of zinc oxide (ZnO), which is one of the most typical random laser semiconductors, brings a low-threshold and quasisingle mode random lasing emission . This phenomenon is due to optical confinement of scattered light inside the defect point.…”
Section: Introductionmentioning
confidence: 99%
“…On behalf of its merits arising from the randomness, a random laser intrinsically has difficulties in controlling its lasing characteristics such as frequency mode, emission intensity, and spatial radiation pattern. Some approaches for passive control of random lasing characteristics, i.e., the modification of scattering properties by designing an adequate random structure, have been reported: For example, Fujiwara et al demonstrated that introducing a defect point of a polystyrene sphere into homogeneous random media consisting of spherical nanoparticles of zinc oxide (ZnO), which is one of the most typical random laser semiconductors, brings a low-threshold and quasisingle mode random lasing emission . This phenomenon is due to optical confinement of scattered light inside the defect point.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor random lasers have significant advantages for applications, such as the possibility of electrical excitation [34][35][36]. Various shapes of semiconductor nanostructures as a random laser component have been used: the most common ones are nanoparticles [37][38][39] and nanowires (nanorods) [40][41][42][43][44] with the diameters of a few hundred nanometers. In this system, multiple light-scattering between nanostructures and subsequent optical amplification contribute to lasing oscillation.…”
Section: Introductionmentioning
confidence: 99%